The Influence of Job Satisfaction on Talent Retention: A Comparative Case Study - Tran, Phuong Dung (My University, 2017)
Since “the war for talent” becomes a prevalent phenomenon in today’s business environment, talent retention is crucial to the organizations for achieving competitive advantage in order to develop sustainably. Reasons for staying in the company of talents are various and discussed in different perspectives. Job satisfaction (JS) is one of the important aspect determining employee’s retention. This research aims to explore how job satisfaction and its factors influence talent retention. In addition, the comparisons of these influences are discovered, one is between a multinational company and a small medium-sized company, second is between Finnish and non-Finnish employees. In order to answer the research questions, an exploratory qualitative method was employed through two case studies. Data was collected from ten semi-structured interviews (five of each company). To reach the purpose of the research, interviewees are both Finnish and non-Finnish employees. They are from middle and senior levels and have certain experience in their own professions. Through the empirical study, it is found that job satisfaction affects significantly the propensity to stay or leave the company. Nature of the job has the most influence on the overall job satisfaction (OJS) and the motivation to continue their current job. The business sizes and types mediate the influence of job satisfaction factors on talent retention. The differences mainly occur in such factors as compensation, nature of the job, working conditions, training and career development, promotion chances. Cultural differences and language barriers may influence foreign employees’ OJS in communication and promotion chances, but those do not affect significantly their turnover intentions. The impact of JS factors on turnover intentions is different between Finnish and non-Finnish employees regarding to the organizational reputation and operation conditions as well as the need for achievement.
Keywords: Human Resource Management; Talent Management; Talent Retention; Job Satisfaction.; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|